2003
DOI: 10.1002/cmr.b.10057
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer transverse gradient coil design

Abstract: ABSTRACT:In small, cylindrical gradient coils consisting of a single layer of wires, the limiting factor in achieving large magnetic field gradients is the rapid increase in coil resistance with efficiency. This behavior results from the decrease in the maximum usable wire diameter as the number of turns is increased. By adopting a multilayer design in which the coil wires are allowed to spread out into multiple layers wound at increasing radii, a more favorable scaling of resistance with efficiency is achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Mathematically, the expression for the current basis function f n (r) is then [9] where N n is the number of triangles in a particular current element and ⌬ ni denotes an i th triangle belonging to node n. To simplify notations, we rewrite Eq. [9] as: [10] where v ni ϭ e ni /(͉e ni ͉͉d ni ͉). Clearly, the divergence of f n (r) is zero and the flux through the edges containing the selected node is unity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathematically, the expression for the current basis function f n (r) is then [9] where N n is the number of triangles in a particular current element and ⌬ ni denotes an i th triangle belonging to node n. To simplify notations, we rewrite Eq. [9] as: [10] where v ni ϭ e ni /(͉e ni ͉͉d ni ͉). Clearly, the divergence of f n (r) is zero and the flux through the edges containing the selected node is unity.…”
Section: Methodsmentioning
confidence: 99%
“…Leggett et al (10) investigated the multilayer transverse cylindrical gradient coils. They also relied on a Fourier series expansion of the current.…”
Section: Introductionmentioning
confidence: 99%
“…Carlson's approach is applied to generate coils of finite length (17). The azimuthal component of the current density for instance can be expressed as a sum of orthonormal functions multiplied by the stream function coefficients a nq (18):…”
Section: Methodology Prediction Of Gradient Coil Pattern Based On Expmentioning
confidence: 99%
“…A good level of screening can be achieved in multilayer coils (81,110), and small versions of such coils can yield higher efficiencies at fixed resistance than conventional two-layer (primary and screen) coils, and that performance improves as the number of layers increases. Simulations showed by Legget et al (81) showed that by optimizing multilayer coils for cooling it is possible to achieve significantly higher gradient strengths at a fixed maximum operating temperature.…”
Section: Other Geometries and Necessitiesmentioning
confidence: 98%